Miejsce i rola przywództwa w kompleksowym zarządzaniu jakością - Karaszewski, Robert; Zastempowski, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Providing effective leadership constitutes a great challenge in companies attempting to implement TQM concepts successfully. It is commonly believed that achieving particular objectives by companies is essentially determined by leadership traits of the company's managerial staff - their attitude, qualifications, creativity and charismatic abilities of evoking expected behavior in working teams. Although there exists certain unanimity in defining the role of a leader, various stereotypes of expected individual leaders' traits can be found worldwide. One can clearly spot in this area the impact of cultural, psychological and social factors. Currently, at the beginning of the third millennium, it is commonly expected that team leaders possess excellent leadership qualities, not to mention that it is taken for granted that every member of top-management must be an effective leader. The importance of this issue is clearly emphasized not only by TQM philosophy but also by Six Sigma, BPR, or even by the updated ISO 9000:2000 standards. Interest paid in the factors contributing to effective leadership is so intense that literally thousands of seminars and trainings are held each year. Books on leadership problems are equally popular to books by most popular authors dealing with fiction. However, it is paradoxical that it is extremely hard to explicitly define what leadership is and what type of qualities a leader should possess. The paper is an attempt to define the expected qualities of leaders in a complex quality management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 88-97